The Evolved Psychology of Psychedelic Set and Setting: Inferences Regarding the Roles of Shamanism and Entheogenic Ecopsychology - Winkelman, Michael James (Frontiers in Pharmacology, 2021)
This review illustrates the relevance of shamanism and its evolution under effects of psilocybin as a framework for identifying evolved aspects of psychedelic set and setting. Effects of 5HT2 psychedelics on serotonin, stress adaptation, visual systems and personality illustrate adaptive mechanisms through which psychedelics could have enhanced hominin evolution as an environmental factor influencing selection for features of our evolved psychology. Evolutionary psychology perspectives on ritual, shamanism and psychedelics provides bases for inferences regarding psychedelics’ likely roles in hominin evolution as exogenous neurotransmitter sources through their effects in selection for innate dispositions for psychedelic set and setting. Psychedelics stimulate ancient brain structures and innate modular thought modules, especially self-awareness, other awareness, “mind reading,” spatial and visual intelligences. The integration of these innate modules are also core features of shamanism. Cross-cultural research illustrates shamanism is an empirical phenomenon of foraging societies, with its ancient basis in collective hominid displays, ritual alterations of consciousness, and endogenous healing responses. Shamanic practices employed psychedelics and manipulated extrapharmacological effects through stimulation of serotonin and dopamine systems and augmenting processes of the reptilian and paleomammalian brains. Differences between chimpanzee maximal displays and shamanic rituals reveal a zone of proximal development in hominin evolution. The evolution of the mimetic capacity for enactment, dance, music, and imitation provided central capacities underlying shamanic performances. Other chimp-human differences in ritualized behaviors are directly related to psychedelic effects and their integration of innate modular thought processes. Psychedelics and other ritual alterations of consciousness stimulate these and other innate responses such as soul flight and death-and-rebirth experiences. These findings provided bases for making inferences regarding foundations of our evolved set, setting and psychology. Shamanic setting is eminently communal with singing, drumming, dancing and dramatic displays. Innate modular thought structures are prominent features of the set of shamanism, exemplified in animism, animal identities, perceptions of spirits, and psychological incorporation of spirit others. A shamanic-informed psychedelic therapy includes: a preparatory set with practices such as sexual abstinence, fasting and dream incubation; a set derived from innate modular cognitive capacities and their integration expressed in a relational animistic worldview; a focus on internal imagery manifesting a presentational intelligence; and spirit relations involving incorporation of animals as personal powers. Psychedelic research and treatment can adopt this shamanic biogenetic paradigm to optimize set, setting and ritual frameworks to enhance psychedelic effects.